Purchasing Decisions Based on Product Quality, Location, and Visual Merchandising - Nursiti; Yopie Yulius; Rizki Riviany Azhariputri (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2025)
This study aims to empirically test whether product quality, location and visual merchandising have an impact on purchasing decisions. The study is based on a theory that supports product quality, location and visual merchandising, and purchasing decisions. This study uses primary data while the samples collected through the convenience method, data obtained through google form to Baper Store customers in Pors with a total of 100 respondents. Data analysis uses outer model, inner model, and hypothesis testing. Novelty in researchers using the sem smartpls 4.1 application, previous studies using SPSS. The results of the hypothesis test study indicate that product quality has a positive effect on product purchasing decisions, location has a negative effect on purchasing decisions and visual merchandising has a negative effect on purchasing decisions. The implications of the study for shop owners are important to provide adequate parking facilities, ensure the safety and comfort of customers who bring vehicles, and arrange the arrangement of goods in a more organized and neat manner. By improving these aspects, it is hoped that the store can increase the appeal and shopping experience of customers. Abstrak- Penelitian ini bertujuan untuk menguji secara empiris apakah kualitas produk, lokasi dan visual merchandising berdampak terhadap keputusan pembelian. Penelitian dilandaskan teori yang mendukung tentang kualitas produk, lokasi dan visual merchandising, dan keputusan pembelian. Penelitian ini menggunakan data primer sedangkan sampel yang dikumpulkan melalui metode convenience, data diperoleh melalui google form kepada pelanggan Baper Store di Pors dengan jumlah responden sebanyak 100. Data analisis menggunakan outer model, inner model, dan uji hipotesis. Novelty pada peneliti menggunakan aplikasi sem-smartpls 4.1, penelitian sebelumnya menggunakan SPSS. Hasil penelitian uji hipotesis menunjukkan bahwa kualitas produk berpengaruh positif terhadap keputusan pembelian produk, lokasi berpengaruh negatif terhadap keputusan pembelian dan visual merchandising berpengaruh negatif terhadap keputusan pembelian. implikasi dari penelitian bagi pemilik toko penting menyediakan fasilitas parkir yang memadai, memastikan keamanan dan kenyamanan pelanggan yang membawa kendaraan, serta mengatur penataan barang dengan lebih terorganisir dan rapi. Dengan memperbaiki aspek-aspek ini, diharapkan toko dapat meningkatkan daya tarik dan pengalaman berbelanja pelanggan.